Light absorption layer, method for manufacturing light absorption layer, and photoelectric conversion element

By using alloy compounds of Ag, Bi, and I as the light absorption layer in the photoelectric conversion element, and adjusting its proportion and crystal structure, the problem of insufficient energy conversion efficiency of the existing light absorption layer is solved, and a higher energy conversion efficiency is achieved.

JP2025038264AInactive Publication Date: 2025-03-19CITIZEN WATCH CO LTD

Patent Information

Application Number
JP2022022404
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2022-02-16
Publication Date
2025-03-19
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

There is still room for improvement in the energy conversion efficiency of the existing light absorption layer in the photoelectric conversion element.

Method used

The alloy compounds of Ag, Bi, and I are used as the light absorption layer, and the photoelectric conversion efficiency of the light absorption layer is improved by adjusting the ratio of Ag and Bi and the crystal structure. Specifically, the crystal structure of the light absorbing layer is based on the alloy compounds of Ag, Bi, and I. The ratio of Ag and Bi is between 2:1 and 7:2, the maximum peak value is within the range of 11.5°≦2θ≦14.0°, and the maximum peak height is at least twice the sub-maximum peak value.

Benefits of technology

By optimizing the alloy compound structure of Ag, Bi, and I, the energy conversion efficiency of the photoelectric conversion element is significantly improved and the performance of the light absorption layer is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025038264000001_ABST
    Figure 2025038264000001_ABST
Patent Text Reader

Abstract

To provide a film which can increase the conversion efficiency of a photoelectric conversion element by using a photoelectric conversion element for a light absorption layer.SOLUTION: A membrane 13 includes crystals represented by the composition formula AgaBibIc and having a crystal structure in which multiple octahedral units, each formed of six I ions, are connected, and Ag ions or Bi ions are arranged at the center of each octahedral unit. When measured by X-ray diffraction, the strongest peak appears in the range of 11.5°≤2θ≤14.0°.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a light absorbing layer, a method for producing a light absorbing layer, and a photoelectric conversion element. [Background technology]

[0002] Composition formula Ag a Bi b I c A film is known which has a structure in which a plurality of octahedral units each consisting of six iodines (I) are linked together by sharing two I ions on the edges, and is used as a light absorbing layer of a photoelectric conversion element (see, for example, Patent Document 1). The film described in Patent Document 1 can be used as a light absorbing layer of a perovskite solar cell element, and when measured by X-ray diffraction, the maximum peak appears in the range of 25°≦2θ≦35°. The film described in Patent Document 1 has a crystal structure in which when measured by X-ray diffraction, the maximum peak appears in the range of 25°≦2θ≦35°, and therefore does not contain lead or the like, has low toxicity, and is electrically and optically usable. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2018-30730 A Summary of the Invention [Problem to be solved by the invention]

[0004] However, in photoelectric conversion elements that convert energy into electrical energy, such as solar cell elements, further improvement in conversion efficiency is desired.

[0005] The present invention has been made to solve such problems, and has an object to provide a light absorbing layer capable of improving the conversion efficiency of a photoelectric conversion element by using the light absorbing layer in the photoelectric conversion element. [Means for solving the problem]

[0006] The light absorbing layer according to the present invention has the composition formula Ag a Bi b I c The compound has a crystal structure in which a plurality of octahedral units, each of which is composed of six I ions, are linked together, and either an Ag ion or a Bi ion is disposed at the center of each of the plurality of octahedral units. When measured by X-ray diffraction, the maximum peak appears in the range of 11.5°≦2θ≦14.0°.

[0007] Furthermore, in the light absorbing layer according to the present invention, in the composition formula, the composition ratios a and b preferably satisfy 2≦a / b≦7 / 2.

[0008] Furthermore, in the light absorbing layer according to the present invention, the height of the maximum peak is preferably at least twice the height of the next highest peak after the maximum peak.

[0009] The photoelectric conversion element according to the present invention further comprises a film having a composition formula of Ag a Bi b I c the light absorbing layer includes a crystal represented by the formula (I), an electron transport layer formed on one surface of the light absorbing layer, and a hole transport layer formed on the other surface of the light absorbing layer, and when measured by X-ray diffraction, the light absorbing layer has a maximum peak in the range of 11.5°≦2θ≦14.0°.

[0010] Furthermore, in the photoelectric conversion element according to the present invention, it is preferable that the composition ratios a and b in the composition formula satisfy 2≦a / b≦7 / 2.

[0011] Furthermore, in the photoelectric conversion element according to the present invention, the height of the maximum peak is preferably at least twice the height of the next highest peak after the maximum peak.

[0012] In addition, a method for forming a light absorbing layer according to the present invention includes disposing a base material in an atmosphere filled with an inert gas and a vaporized first organic substance, and forming a compound having a composition formula of Ag a Bi b I cand a solvent containing an organic substance different from the first organic substance, onto a surface of a substrate, and baking the substrate having the precursor solution applied to its surface to form a light absorbing layer.

[0013] Furthermore, it is preferable that the method for producing a light absorbing layer according to the present invention further includes dropping a second organic substance different from the organic substance contained in the solvent onto the surface of the substrate as a poor solvent while applying the precursor solution to the surface of the substrate.

[0014] Furthermore, in the method for manufacturing a light absorbing layer according to the present invention, the second organic substance is preferably chlorobenzene.

[0015] Furthermore, in the method for manufacturing a light absorbing layer according to the present invention, the first organic substance is preferably chlorobenzene. Effect of the Invention

[0016] The light absorbing layer according to the present invention can improve the conversion efficiency of a photoelectric conversion element by using it as the light absorbing layer of the photoelectric conversion element. [Brief description of the drawings]

[0017] [Figure 1] 1 is a cross-sectional view of a photoelectric conversion element 1 according to an embodiment. [Diagram 2] FIG. 2 is a diagram showing a crystal structure included in the light absorbing layer shown in FIG. 1, where (a) shows a (003) plane in a unit cell included in the light absorbing layer shown in FIG. 1, and (b) is a perspective view of an octahedral unit included in the light absorbing layer shown in FIG. 1. [Diagram 3] 2 is a flowchart showing a method for manufacturing the photoelectric conversion element shown in FIG. [Figure 4] 4 is a flowchart showing a more detailed process of the light absorbing layer forming step shown in S104 in FIG. 3. [Diagram 5] FIG. 2(a) shows the X-ray diffraction pattern of Example 1, and (b) shows the X-ray diffraction pattern of the comparative example. [Figure 6]FIG. 1 shows an X-ray diffraction pattern of Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] Hereinafter, preferred embodiments of the light absorbing layer and the photoelectric conversion element according to the present invention will be described with reference to the drawings. However, it should be noted that the technical scope of the present invention is not limited to these embodiments, but covers the inventions described in the claims and their equivalents.

[0019] The term "photoelectric conversion element" refers to an element that converts light energy into electrical energy, and includes solar cell elements, photocell elements, and photovoltaic elements that convert light energy, including indoor light and sunlight, into electrical energy. The photoelectric conversion element according to the embodiment may be used as a solar cell module, also called a solar panel, and a power supply device for portable devices and the like.

[0020] FIG. 1 is a cross-sectional view of a photoelectric conversion element according to an embodiment.

[0021] The photoelectric conversion element 1 has a substrate 10, a lower conductive layer 11, an electron transport layer 12, a light absorbing layer 13, a hole transport layer 14, and an upper electrode 15, and the lower conductive layer 11, the electron transport layer 12, the light absorbing layer 13, the hole transport layer 14, and the upper electrode 15 are sequentially stacked on the substrate 10. The photoelectric conversion element 1 is a forward structure solar cell element that generates a voltage between the lower conductive layer 11 and the upper electrode 15 in response to light being incident through the substrate 10 and the lower conductive layer 11, and outputs a current from the upper electrode 15.

[0022] The substrate 10 is capable of supporting the components included in the photoelectric conversion element 1, such as an insulating glass substrate, and is formed of a transparent material that transmits incident light incident on the photoelectric conversion element 1. The transparent material is a material that transmits light of a wavelength absorbed by the light absorbing layer 13, and is preferably a material having a transmittance of 80% or more for light in the wavelength region absorbed by the light absorbing layer 13, and more preferably a material having a transmittance of 95% or more for light in the wavelength region absorbed by the light absorbing layer 13. The substrate 10 may be formed of a conductive material.

[0023] The lower conductive layer 11 is formed on the substrate 10 so as to cover the substrate 10, using a material that is transparent like the substrate 10 and can transport electrons with high efficiency, for example, a low resistance material with a sheet resistance of 10Ω or less. The lower conductive layer 11 is formed, for example, as a thin film made of fluorine-doped tin oxide (FTO), which has a small change in resistivity due to high-temperature heat treatment, is transparent, and has high conductivity. The lower conductive layer 11 may also be a thin film made of tin-doped indium oxide (ITO), aluminum-doped zinc oxide (AZO), gallium-doped zinc oxide (GZO), or niobium-doped titanium oxide (NTO). The lower conductive layer 11 preferably has a thickness of 0.01 μm or more and 10.0 μm or less, and more preferably has a thickness of 0.05 μm or more and 1.0 μm or less.

[0024] The electron transport layer 12 is an n-type semiconductor that blocks holes generated in the light absorption layer 13 and transports electrons generated in the light absorption layer 13 to the lower conductive layer 11 with high efficiency, and is formed on the lower conductive layer 11 so as to cover the lower conductive layer 11. The electron transport layer 12 is preferably formed of a material with high electron transport properties. The electron transport layer 12 is formed of a metal oxide such as titanium oxide (TiO2, etc.), tin oxide (SnO2, etc.), tungsten oxide (WO2, etc.), zinc oxide (ZnO), and aluminum oxide (Al2O3). The electron transport layer 12 preferably has a thickness of 5 nm or more and 200 nm or less, and more preferably has a thickness of 20 nm or more and 60 nm or less.

[0025] The light absorbing layer 13 has the composition formula Ag a Bi b I c The electron transport layer 12 is formed of a material represented by the formula: a Bi b I cIn the formula, a, b, and c represent composition ratios, satisfying c=a+3b, and preferably 2≦a / b≦7 / 2, more preferably a / b=7 / 2. The light absorbing layer 13 preferably has a thickness of 10 nm or more and 10,000 nm or less, more preferably 20 nm or more and 900 nm or less. The light absorbing layer 13 absorbs light incident through the lower conductive layer 11 and the electron transport layer 12, and electrons are excited by the absorbed light, and electrons and holes are generated inside. The holes generated inside the light absorbing layer 13 are transported to the upper electrode 15 through the hole transport layer 14, and the electrons generated inside the light absorbing layer 13 are transported to the lower conductive layer 11 through the electron transport layer 12, and the photoelectric conversion element 1 generates an electromotive force.

[0026] The structure of the crystals contained in the light absorbing layer 13 is measured by X-ray diffraction etc. The light absorbing layer 13 is subjected to X-ray diffraction measurement using an X-ray diffractometer such as SmartLab manufactured by Rigaku Corporation under the following measurement conditions. (Measurement conditions) X-ray source:CuKα X-ray wavelength: 1.5405Å, 1.5443Å Measurement range: 2θ=10~70° Measurement step width: 0.02° Scan speed: 1.0 deg / min Measurement temperature: normal temperature

[0027] In the light absorbing layer 13, the maximum peak appears in the range of 11.5°≦2θ≦14.0°, more specifically, at 12.76°. The angle at which the maximum peak appears is the angle corresponding to the (003) plane. The height of the first peak, which is the maximum peak, is preferably at least twice the height of the second peak, which is the next highest peak, and more preferably at least 2.5 times the height of the second peak. The height of the first peak is more preferably at least three times the height of the second peak, and more preferably at least 3.5 times the height of the second peak.

[0028] 2 is a diagram showing a crystal structure 20 contained in the light absorbing layer 13. Fig. 2(a) shows the (003) plane in a unit cell contained in the light absorbing layer 13, and Fig. 2(b) is a perspective view of an octahedral unit contained in the light absorbing layer 13.

[0029] The crystal contained in the light absorbing layer 13 is a trigonal crystal in which octahedral unit structures are linked. I ions 22 are arranged at each of the six vertices of the octahedral unit 21, and either an Ag ion 23 or a Bi ion 23 is arranged at the center of the octahedral unit 21. The unit cell contained in the crystal structure 20 of the crystal contained in the light absorbing layer 13 has lengths of 4.35 Å in the a-axis and b-axis directions and a length of 20.81 Å in the c-axis direction. The I ion 22 contained in one octahedral unit 21 is shared with another adjacent octahedral unit 21.

[0030] The crystals contained in the light absorbing layer 13 have a crystal structure 20 in which the maximum peak is in the range of 11.5°≦2θ≦14.0° when measured by X-ray diffraction, and therefore the arrangement of atoms arranged on the (003) plane 24 is uniform, that is, formed to have the highest orderliness. The crystals contained in the light absorbing layer 13 have a high degree of order in the c-axis direction, since the arrangement of atoms arranged on the (003) plane 24 is highly orderly.

[0031] The hole transport layer 14 is made of selenium, iodides such as copper iodide (CuI), cobalt complexes such as layered cobalt oxide, CuSCN, molybdenum oxide (MoO3, etc.), nickel oxide (NiO, etc.), 4CuBr·3S (C4H9), organic hole transport materials, etc. Examples of the organic hole transport materials include polythiophene derivatives such as poly-3-hexylthiophene (P3HT) and polyethylenedioxythiophene (PEDOT), fluorene derivatives such as 2,2',7,7'-tetrakis-(N,N-di-p-methoxyphenylamine)-9,9'-spirobifluorene (spiro-MeO-TAD), carbazole derivatives such as polyvinylcarbazole, triphenylamine derivatives such as poly[bis(4-phenyl)(2,4,6-triphenylmethyl)amine] (PTAA), diphenylamine derivatives, polysilane derivatives, polyaniline derivatives, etc. The thickness of the hole transport layer 14 is not particularly limited, but is preferably 0.01 μm or more and 10 μm or less.

[0032] The upper electrode 15 is a metal layer such as a gold layer (Au) and is formed on the hole transport layer 14. The upper electrode 15 may be a Ti / Au layer in which a gold layer (Au) is formed on a titanium (Ti) layer. The upper electrode 15 may be formed of any material that comes into contact with the hole transport layer 14, and may be formed of a metal such as Au, Pt, Ni, etc. having a relatively large work function, or a carbon-based electrode such as graphite. The upper electrode 15 preferably has a thickness of 2 nm to 200 nm. When the thickness of the upper electrode 15 is thinner than 2 nm, the resistance value in the extension direction of the upper electrode 15 increases, the collection efficiency of holes decreases, and the conversion efficiency of the photoelectric conversion element 1 decreases. When the thickness of the upper electrode 15 is thicker than 200 nm, the resistance value in the film thickness direction of the upper electrode 15 increases, the conversion efficiency of the photoelectric conversion element 1 decreases, and the amount of material forming the upper electrode 15 increases, resulting in high manufacturing costs.

[0033] FIG. 3 is a flowchart showing a method for manufacturing the photoelectric conversion element 1.

[0034] First, in a substrate preparation step, a substrate is prepared (S101). The substrate prepared in the substrate preparation step is, for example, a flat glass substrate having an FTO formed on one surface. The glass substrate is an example of a substrate 10, and the FTO is an example of a lower conductive layer 11. The substrate prepared in the substrate preparation step is preferably subjected to a cleaning process such as a UV ozone cleaning process.

[0035] Next, in the electron transport layer formation step, the electron transport layer 12 is formed on the FTO (S102). The electron transport layer 12 is formed by forming a first layer by spray pyrolysis, immersing the substrate in an aqueous titanium tetrachloride solution, and then baking the substrate for a predetermined time to form a second layer.

[0036] In the process of S102, in the spray pyrolysis method for forming the first layer, the substrate prepared in the substrate preparation step is heated at a predetermined temperature, a solution containing a titanium chelate compound is sprayed onto the FTO, and then the substrate is baked at a predetermined temperature for a predetermined time. The titanium chelate compound sprayed onto the substrate in the spray pyrolysis method is, for example, tetrakis(2,4-pentanedionato)titanium(IV) and diisopropoxytitanium(IV)bis(acetylacetonate). The heating temperature in the spray pyrolysis method is preferably 300°C or higher and 600°C or lower, more preferably 400°C or higher and 500°C or lower. The heating temperature when the substrate is heated after the solution containing the titanium chelate compound is sprayed onto the FTO is preferably 300°C or higher and 900°C or lower, more preferably 450°C or higher and 550°C or lower. Furthermore, the heating time when the substrate is heated after the solution containing the titanium chelate compound is sprayed onto the FTO is preferably 30 minutes or more and 600 minutes or less, more preferably 60 minutes or more and 180 minutes or less. The firing temperature at which the substrate is fired when the second layer is formed is preferably 300° C. or more and 900° C. or less, more preferably 450° C. or more and 550° C. or less. The firing time at which the substrate is fired when the second layer is formed is preferably 20 minutes or more and 600 minutes or less, more preferably 60 minutes or more and 180 minutes or less.

[0037] Next, in the interface treatment step, the surface of the electron transport layer 12 formed on the substrate 10 is treated with an interface treatment (S103). The interface treatment shown in S103 is performed, for example, by applying a silane coupling agent by spin coating. In the interface treatment in S103, the rotation speed in the spin coating is preferably 500 rpm or more and 3000 rpm or less, and more preferably 1000 rpm or more and 2000 rpm or less. In the interface treatment in S103, the baking temperature after the spin coating is preferably 50° C. or more and 150° C. or less, and more preferably 80° C. or more and 120° C. or less. In the interface treatment in S103, the baking time after the spin coating is preferably 1 minute or more and 30 minutes or less, and more preferably 3 minutes or more and 10 minutes or less.

[0038] Next, in the light absorbing layer forming step, the light absorbing layer 13 is formed on the electron transport layer 12 that has been subjected to the interface treatment in S103 (S104). The substrate 10 on which the electron transport layer 12 is laminated is an example of a base material on which a light absorbing layer is formed.

[0039] FIG. 4 is a flowchart showing the detailed process of the light absorbing layer forming step S104.

[0040] First, the first organic substance is vaporized in the atmosphere inside the housing filled with an inert gas, and the vapor concentration of the first organic substance inside the housing is adjusted (S201). The inert gas filled inside the housing is, for example, a rare gas such as argon, and nitrogen gas. The internal pressure of the housing is preferably 95,000 Pa or more and 105,000 Pa or less, and more preferably 100,000 Pa or more and 103,500 Pa or less. In the process of S202, the first organic substance injected into the housing is, for example, chlorobenzene, chloromethane, IPA, and mixtures thereof, with chlorobenzene being preferred. Also, the vapor concentration of the first organic substance is 1 m when the internal pressure of the housing is 101,325 Pa. 3It is preferable that the amount of the non-volatile gas is 0.01 g or more and 10 g or less, and more preferably 0.1 g or more and 5 g or less.

[0041] Next, the substrate 10 on which the electron transport layer 12 is formed after the interface treatment in S103 is placed in the atmosphere inside a housing filled with an inert gas and the vaporized first organic substance after the vapor concentration of the first organic substance has been adjusted in the treatment in S201 (S202). In the treatment shown in S201, the housing in which the substrate 10 is placed is, for example, a glove box.

[0042] Next, the composition formula Ag a Bi b I c A precursor solution containing a precursor capable of forming a crystal represented by the formula (I) and a solvent containing an organic substance different from the first organic substance is applied to the surface of the electron transport layer 12 formed on the substrate 10 (S203). The precursors contained in the precursor solution are AgI and BiI3. The content ratio of AgI and BiI3 is preferably in the range of 2:1 to 7:2 for AgI:BiI3. The solvent contained in the precursor solution is, for example, dimethyl sulfoxide (DMSO), dimethylformamide (DMF), and n-butylamine, with dimethyl sulfoxide being preferred.

[0043] The precursor solution is formed into a film by, for example, spin coating on the electron transport layer 12. In the process shown in S203, the rotation speed in the spin coating is preferably 500 rpm or more and 3000 rpm or less, and more preferably 1000 rpm or more and 2000 rpm or less.

[0044] Next, while the precursor solution is being applied to the surface of the base material, a second organic substance different from the organic substance contained in the solvent of the precursor solution is dropped as a poor solvent onto the surface of the light absorbing layer 13 formed on the substrate 10 (S204). In the process of S204, the second organic substance dropped onto the light absorbing layer 13 is, for example, chlorobenzene and benzene, with chlorobenzene being preferred.

[0045] Then, the substrate 10 on which the precursor solution is applied to the surface of the electron transport layer 12 and the second organic material is dropped onto the surface of the electron transport layer 12 is baked (S205), thereby forming the light absorbing layer 13 on the surface of the electron transport layer 12. In the process shown in S205, the baking temperature after the spin coating is preferably 50° C. or more and 180° C. or less, and more preferably 90° C. or more and 120° C. or less. Moreover, the baking time after the spin coating is preferably 1 minute or more and 180 minutes or less, and more preferably 30 minutes or more and 90 minutes or less. Moreover, in the process shown in S205, the substrate 10 may be baked at a plurality of temperatures.

[0046] Next, in the hole transport layer forming step, the hole transport layer 14 is formed on the light absorbing layer 13 (S105). The hole transport layer forming step shown in S105 is performed by applying a solution in which Spiro-OMeTAD is dissolved in chlorobenzene by spin coating, for example. In the interface treatment in S105, the rotation speed in the spin coating is preferably 1000 rpm or more and 5000 rpm or less, and more preferably 2000 rpm or more and 4000 rpm or less. In the hole transport layer forming step in S105, the baking temperature after the spin coating is preferably 20° C. or more and 180° C. or less, and more preferably 80° C. or more and 120° C. or less. In the hole transport layer forming step in S105, the baking time after the spin coating is preferably 1 minute or more and 180 minutes or less, and more preferably 30 minutes or more and 90 minutes or less.

[0047] Then, in an upper electrode deposition step, the upper electrode 15 is deposited on the hole transport layer 14 (S106), thereby completing the manufacturing process of the photoelectric conversion element 1. The upper electrode deposition step indicated by S103 is performed by depositing the upper electrode 15 on the hole transport layer 14 by a vacuum deposition method using a metal such as Au, Pt, or Ni.

[0048] Although the photoelectric conversion element 1 is a normal structure type photoelectric conversion element, the photoelectric conversion element according to the embodiment may be an inverted structure type photoelectric conversion element. The inverted structure type photoelectric conversion element has a substrate, a lower conductive layer formed on the substrate, a hole transport layer formed on the lower conductive layer, a light absorbing layer formed on the hole transport layer, an electron transport layer formed on the light absorbing layer, and an upper electrode formed on the electron transport layer. In the inverted structure type photoelectric conversion element, the light absorbing layer has a composition formula of Ag a Bi b I c and when measured by X-ray diffraction, the maximum peak appears in the range of 11.5°≦2θ≦14.0°. In the photoelectric conversion element according to the embodiment, the electron transport layer is formed on one surface of the light absorbing layer, and the hole transport layer is formed on the other surface of the light absorbing layer. EXAMPLES

[0049] (Fabrication of photoelectric conversion element) First, a glass with FTO manufactured by Pexel Technologies, Inc. is prepared. The prepared glass with FTO is UV ozone cleaned for 20 minutes. Next, a solution containing tetrakis(2,4-pentanedionato)titanium(IV) heated to 450°C on a hot plate is sprayed onto the FTO of the UV ozone cleaned glass with FTO. The glass with FTO sprayed with tetrakis(2,4-pentanedionato)titanium(IV) is fired at 500°C for 1 hour. The glass with FTO fired at 500°C is immersed in an aqueous solution of titanium tetrachloride, and then fired at 500°C for 1 hour to form an electron transport layer on the FTO. The glass with FTO with the electron transport layer formed on the FTO is UV ozone cleaned for 20 minutes. Next, a silane coupling agent, model number KBE-903, manufactured by Shin-Etsu Chemical Co., Ltd., is spin-coated at 1500 rpm, and then baked at 100° C. for 5 minutes to perform an interface treatment on the electron transport layer formed on the FTO.

[0050] The FTO-attached glass with the electron transport layer subjected to interface treatment is moved into a glove box filled with nitrogen, and the light absorbing layer is formed. Examples 1-2 and Comparative Example differ in the film formation conditions under which the light absorbing layer is formed. In Example 1 and Comparative Example, AgI and BiI3 are contained in the solute of the precursor solution at a ratio of 7:2, and Ag and Bi are contained in the light absorbing layer at a ratio of 7:2. In Example 2, AgI and BiI3 are contained in the solute of the precursor solution at a ratio of 2:1. In Examples 1-2, the light absorbing layer forming process is performed in an atmosphere of 1 m 3 The precursor solution contains 0.5 g of chlorobenzene vapor per gram of nitrogen per unit volume. On the other hand, in the comparative example, the atmosphere in which the light absorbing layer forming step is performed does not contain chlorobenzene vapor. In the examples 1 and 2 and the comparative example, the solvent of the precursor solution is dimethyl sulfoxide.

[0051] The glass with FTO is moved into the glove box, and a light absorbing layer is formed on the interface-treated electron transport layer by spin coating. The glass with FTO is rotated at 1500 rpm and the precursor solution is applied to it. In Examples 1 and 2, the atmosphere of the preparation environment is controlled by the concentration of chlorobenzene. On the other hand, in the comparative example, the atmosphere of the preparation environment is nitrogen. In Examples 1 and 2 and the comparative example, the glass with FTO is baked at 90°C for 5 minutes after the precursor solution is applied, and then baked at 120°C for 1 hour to form a light absorbing layer.

[0052] The FTO-attached glass on which the light absorption layer has been formed is taken out of the glove box, and the hole transport layer is formed by spin coating. When the hole transport layer is formed, the FTO-attached glass is rotated at 3000 rpm, and a solution of Spiro-OMeTAD dissolved in chlorobenzene is applied to the glass. Then, the FTO-attached glass on which the hole transport layer has been formed has an upper electrode formed on the hole transport layer by vacuum deposition.

[0053] Examples 1 to 2 and Comparative Example X-ray diffraction and power generation efficiency were measured under the following measurement conditions. (X-ray diffraction measurement conditions) Measurement equipment: Rigaku SmartLab X-ray source:CuKα X-ray wavelength: 1.5405Å, 1.5443Å Measurement range: 2θ=10~70° Measurement step width: 0.02° Scan speed: 1.0 deg / min Measurement temperature: normal temperature (Conditions for measuring power generation efficiency) Light source: BLD-100 manufactured by Bunkoukeiki Co., Ltd. Illuminance rating: 200 Lux Light receiving area: 6.25mm 2

[0054] Table 1 shows the content ratio of Ag and Bi in the light absorbing layer, the concentration of chlorobenzene in the atmosphere in the light absorbing layer forming process, and the power generation efficiency in Examples 1 and 2 and Comparative Example. In Table 1, the concentration of chlorobenzene in the atmosphere in the light absorbing layer forming process is high, and the concentration is 1 m 3 This indicates that the vapor content of chlorobenzene is 0.5 g per unit of nitrogen.

[0055] [Table 1]

[0056] The power generation efficiency of Example 1 is 5.0%, and the power generation efficiency of Example 2 is 4.6%, and the power generation efficiency of Examples 1 and 2 is higher than the power generation efficiency of the comparative example, which is 0.5%.

[0057] In the comparative example, when a solution in which AgI and BiI3 are dissolved in a good solvent having high solubility is applied and then baked, the glass with FTO is heated and the temperature rises, so the film containing AgI and BiI3 is re-dissolved by the good solvent remaining in the film. In the comparative example, it is presumed that the quality of the crystals of AgI and BiI3 deteriorates because the film containing AgI and BiI3 is re-dissolved when the glass with FTO is heated.

[0058] On the other hand, in Examples 1 and 2, the atmosphere in the preparation environment is controlled by the concentration of chlorobenzene. In Examples 1 and 2, the light absorbing layer is prepared in an atmosphere with a high concentration of chlorobenzene, so it is presumed that chlorobenzene forms an intermediate with AgI or BiI3 to enhance the order in the (003) plane, and the light absorbing layer is formed as a high-quality crystalline film, improving the power generation efficiency.

[0059] Fig. 5(a) shows the X-ray diffraction pattern of Example 1, Fig. 5(b) shows the X-ray diffraction pattern of the Comparative Example, and Fig. 6 shows the X-ray diffraction pattern of Example 2. In Figs. 5(a), 5(b), and 6, the horizontal axis is the diffraction angle 2θ, and the vertical axis is the X-ray intensity. Arrow A indicates the X-ray diffraction pattern appearing at 12.76°, which is an angle corresponding to the (003) plane, and arrow B indicates the X-ray diffraction pattern appearing at 29.28°, which is an angle corresponding to the (104) plane.

[0060] In Examples 1 and 2, the peak appearing in the range of 11.5°≦2θ≦14.0°, specifically at 12.76°, is higher than the other peaks and is the first peak, which is the maximum peak of the X-ray diffraction pattern. The peak appearing at 29.28° is the second peak, which is the next highest peak after the first peak. The peak appearing at 12.76°, which is the angle corresponding to the (003) plane, is the maximum peak, and it is presumed that Examples 1 and 2 have a high order in the c-axis direction. It is presumed that Examples 1 and 2 have a high order in the c-axis direction and reduce defects in the crystals contained in the light absorbing layer 13, thereby reducing the loss due to recombination between electrons and holes generated by light absorption, and improving the transport performance to improve the power generation efficiency. In Example 1, the height of the first peak is about 3.8 times the height of the second peak, and in Example 2, the height of the first peak is about 2.3 times the height of the second peak.

[0061] On the other hand, in the comparative example, the peak appearing at 12.76° is not the maximum peak of the X-ray diffraction pattern, and it is presumed that the order in the c-axis direction is not high. In the comparative example, the order in the c-axis direction is low, and many defects are formed in the crystals contained in the light absorbing layer 13, which is presumed to increase the loss due to recombination between electrons and holes generated by light absorption and to reduce the power generation efficiency due to the deterioration of the transport performance. In the comparative example, the height of the first peak is about 0.9 times the height of the second peak. [Explanation of symbols]

[0062] 1 Photoelectric conversion element 10 Substrate 11 Lower conductive layer 12 Electron transport layer 13 Light absorbing layer 14 Hole transport layer 15 Upper electrode

Claims

1. Composition formula Ag a Bi b I c The present invention relates to a crystal having a structure in which a plurality of octahedral units each consisting of six I ions are connected together, and either an Ag ion or a Bi ion is disposed at the center of each of the plurality of octahedral units, When measured by X-ray diffraction, the maximum peak appears in the range of 11.5°≦2θ≦14.0°. A light absorbing layer comprising:

2. 2. The light-absorbing layer according to claim 1, wherein in the composition formula, the composition ratios a and b satisfy 2≦a / b≦7 / 2.

3. The light-absorbing layer according to claim 1 , wherein the height of the maximum peak is at least twice the height of the next highest peak after the maximum peak.

4. Composition formula Ag a Bi b I c A light absorbing layer including a crystal represented by the formula: an electron transport layer formed on one surface of the light absorbing layer; a hole transport layer formed on the other surface of the light absorbing layer; When the light absorbing layer is measured by X-ray diffraction, a maximum peak appears in the range of 11.5°≦2θ≦14.0°. A photoelectric conversion element comprising:

5. 5. The photoelectric conversion element according to claim 4, wherein in the composition formula, the composition ratios a and b satisfy 2≦a / b≦7 / 2.

6. 6. The photoelectric conversion element according to claim 4, wherein the height of the maximum peak is at least twice the height of the next highest peak after the maximum peak.

7. A substrate is placed in an atmosphere filled with an inert gas and a vaporized first organic substance; Composition formula Ag a Bi b I c A precursor solution containing a precursor capable of forming a crystal represented by the formula (I) and a solvent containing a second organic substance different from the first organic substance is applied to a surface of a substrate; The precursor solution is applied to the surface of a substrate, and the substrate is baked to form a light absorbing layer. A method for forming a light absorbing layer comprising the steps of:

8. The method for forming a light absorbing layer according to claim 7 , further comprising: dropping a second organic substance different from the organic substance contained in the solvent onto the surface of the substrate as a poor solvent while applying the precursor solution to the surface of the substrate.

9. The method for forming a light absorbing layer according to claim 8 , wherein the second organic substance is chlorobenzene.

10. 10. The method for forming a light absorbing layer according to claim 7, wherein the first organic substance is chlorobenzene.

Citation Information

Patent Citations

  • Film, optical device, electronic device, photoelectric conversion apparatus, and film production method

    JP2018030730A

Cited By

  • Method for manufacturing a hot air processed rudorffite absorber and method for manufacturing a photovoltaic device comprising the same

    KR102920401B1